WACANA PEMBERIAN KEWENANGAN FIAT EKSEKUSI KEPADA PENGADILAN TATA USAHA NEGARA ATAS HASIL PENYELESAIAN SENGKETA ADMINISTRASI PEMERINTAHAN DI LUAR PENGADILAN - Muhammad Adiguna Bimasakti (Jurnal Hukum Peratun, 2022)
The existence of institutions outside the state administrative courts that have the authority to resolve government administrative disputes has in recent years caused several problems. Among them are regarding the implementation or execution of the results of dispute resolution which mechanism is not clear. Finally, some parties tried to evade law (Fraude la lois) on the process of implementing the results of the settlement of administrative disputes outside the court, for example by filing a lawsuit regarding government's real act in the administrative court, when in fact the object of the dispute was not a real act. This kind of legal evading practice, if left unchecked, can disrupt the legal system of administration, including the procedural law of the administrative court, so it must be accommodated in formal administrative law (procedural law) appropriately. Because in fact, if it is not properly regulated in formal law, this will become a continuous polemic. One of the solutions offered in this paper is to add the authority of the administrative court as the giver of fiat execution for the implementation of the results of the settlement of administrative disputes that have been settled out of court based on statutory regulations. Among them are the fiat execution of the results of administrative proceedings, the implementation of the Ombudsman's recommendations and the implementation of the Ombudsman's decision.